Strategi Komunikasi Islam Felix Siauw di Instagram - Ulfa Khairani (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2020)
This study aims to review how the Islamic communication strategy carried out by Ust. Felix Siauw on Instagram as a media of preaching. As one of the famous da'i who is close to young people and active in social media, Felix Siauw has his own uniqueness in managing his social media accounts. This paper uses a qualitative descriptive description. Data collection techniques using documentation and observation. The determination of informant data is based on purposive sampling technique. The number of informants used as the primary data consisted of the last 30 feeds consisting of photos and videos. The results showed that Ustadz Felix Siauw used Instagram by focusing on structuring feeds and using photo filters to attract millennials as mad'u (communicants). Ustadz Felix Siauw also uses effective communication in building Islamic communication with other Instagram users by writing communicative and informative captions as well as opening communication between users through communication styles, use of filters and feed settings, photos and videos, and captions.